Persepsi Resiko Bencana Alam Ditinjau dari Sentralitas Jaringan Informasi Kebencanaan - Sapta Widi Wusana; Rahmat Hidayat (Jurnal Ilmu Perilaku, 2017)
This research aims to understand the risk perception of Merapi disaster in hazardous community, based on social network centrality. Quantitative approach with psychology scale is used to reveal perceptions of volcanic risk of Merapi, collaborated with name generator to reveal index of social network centrality from 83 people. Result of this research proves that degree, betweeness, closeness, and eigenvector centrality all together are able to predict Merapi’s disaster risk perception, with 17% coefficient determination value (R2). Which means that the research hypothesis is convicted. Separately, betweenness, closeness and eigenvector centrality contribute negatively with perceptions of Merapi volcanic risk. Strong, influential and independent actors consider the potential danger of Merapi as predictable and avoidable. The availability of support, information and access further enhances confidence in the ability of the self to control the impact of Merapi exposure. Conversely, peripheral actors have concerns and more assumptions about the dangers of Merapi, which results from a lack of information, access, support that ultimately reduces his beliefs.